Significance of CRP and Procalcitonin Level in the Early Diagnosis of Neonatal Sepsis in Erbil, Iraq - Mohammed Sadiq, Mahmood; Hanna, Sasan Loqa; Kakasur, Media Abdullah (Journal of Neonatal Surgery, 2025)
Background and Objectives: Neonatal sepsis remains a leading cause of morbidity and mortality in developing countries, where timely diagnosis is challenging. This study aimed to evaluate the diagnostic performance of procalcitonin (PCT) compared with C-reactive protein (CRP) and white blood cell (WBC) count in the early detection of neonatal sepsis in Erbil, Iraq. Methods: A hospital-based case-control study was conducted in the Raparin Teaching Hospital for Children between April 2023 and October 2024. A total of 80 neonates (40 with culture-confirmed sepsis and 40 controls) were enrolled. Laboratory investigations included complete blood counts, CRP, and PCT measurement. Diagnostic validity indices were calculated, and receiver operating characteristic (ROC) analysis was performed. Results: PCT levels were significantly higher in septic neonates (773.00 ± 223.01 pg/mL) compared to controls (256.50 ± 137.70 pg/mL, p<0.001). CRP positivity was noted in 36 neonates with sepsis (90.0%) versus 9 controls (22.5%, p=0.002). Mean WBC count was elevated in cases (16.81 ± 2.29 ×10⁹/L) compared to controls (15.15 ± 0.82 ×10⁹/L, p<0.001). CRP demonstrated sensitivity of 90.0% (36/40) and specificity of 77.5% (31/40), while PCT displayed balanced accuracy with sensitivity of 87.5% (35/40) and specificity of 87.5% (35/40). ROC analysis showed the highest discriminatory power for PCT (AUC=0.975, 95% CI: 0.949–0.990), followed by CRP (AUC=0.838) and WBC count (AUC=0.735). Conclusion: PCT outperformed traditional biomarkers in early diagnosis of neonatal sepsis, providing more balanced diagnostic accuracy. Combining PCT with CRP and clinical assessment may optimize prompt identification and management of sepsis in neonates.